Aplikasi produk intelektual kampus dalam bentuk keripik kulit (fish skin) Patin pada UMKM Graha Pratama Fish di Desa Koto Mesjid Kabupaten Kampar - Dewita Dewita; Syahrul Syahrul; Edison Edison; Dahlia Dahlia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
UMKM Graha Pratama Fish in Koto Mesjid village, Kampar district, is one of the partners of LPPM Riau University. This UMKM was originally designed to produce fish-based snacks. Therefore, this PKM activity is directed at fostering, developing and improving product quality that meets SNI standards. This solution will be offered to partners in order to develop their business and improve the quality of their products. The products that have been trained for several years before are fish sago noodles, meatballs, nuggets and fish snacks. Thus, this year's activity is a continuation of the activities of previous years, namely providing training to add product variants, so that PKM activities are emphasized on training on the manufacture of snack food products such as catfish fish skin chips. This product is one of the research products of a lecturer in the Department of Fishery Products Technology, Unri, meaning the campus intellectual product. The method of activity carried out is the extension and experiment method with the implementation stages as follows: (1) The preparation stage, which is to approach partners and provide an explanation of the aims and objectives for carrying out PKM activities. and (2) the implementation stage, namely providing counseling and training to partners, regarding the technology transfer of processing new variants of snacks such as fish skin chips. The outputs of this activity include: i) Increased public understanding of business management, ii) Identification new business opportunities for fish-based processed products to partners, and iii) Publication on online media (electronic) Pekanbaru Pos, as well as scientific articles for community service. n for seminars and publication in nationally accredited journals.